Imaging long distance propagating calcium signals in intact plant leaves with the BRET-based GFP-aequorin reporter - Xiong, Tou Cheu; Ronzier, Elsa; Sanchez, Frédéric; Corratgé-faillie, Claire; Mazars, Christian; Thibaud, Jean-Baptiste (Frontiers in Plant Science, 2014)
Calcium (Ca2+) is a second messenger involved in many plant signalling processes. Biotic and abiotic stimuli induce Ca2+ signals within plant cells, which, when decoded, enable these cells to adapt in response to environmental stresses. Multiple examples of Ca2+ signals from plants containing the fluorescent yellow cameleon sensor (YC) have contributed to the definition of the Ca2+ signature in some cell types such as root hairs, pollen tubes and guard cells. YC is, however, of limited use in highly autofluorescent plant tissues, in particular mesophyll cells. Alternatively, the bioluminescent reporter aequorin enables Ca2+ imaging in the whole plant, including mesophyll cells, but this requires specific devices capable of detecting the low amounts of emitted light. Another type of Ca2+ sensor, referred to as GFP-aequorin (G5A), has been engineered as a chimeric protein, which combines the two photoactive proteins from the jellyfish Aequorea victoria, the green fluorescent protein (GFP) and the bioluminescent protein aequorin. The Ca2+-dependent light-emitting property of G5A is based on a bioluminescence resonance energy transfer (BRET) between aequorin and GFP. G5A has been used for over 10 years for enhanced in vivo detection of Ca2+ signals in animal tissues. Here, we apply G5A in Arabidopsis and show that G5A greatly improves the imaging of Ca2+ dynamics in intact plants. We describe a simple method to image Ca2+ signals in autofluorescent leaves of plants with a cooled charge-coupled device (cooled CCD) camera. We present data demonstrating how plants expressing the G5A probe can be powerful tools for imaging of Ca2+ signals. It is shown that Ca2+ signals propagating over long distances can be visualized in intact plant leaves and are visible mainly in the veins.